Bag Valve Mask Ventilation as a Perceptual-Cognitive Skill. (March 2018) - Mumma, Joel M.; Durso, Francis T.; Dyes, Michelle; dela Cruz, Rogelio; Fox, Valerie P.; Hoey, Mary
Objective: This study used a high-fidelity infant mannequin to examine the relationship between the quality of bag valve mask ventilation (BVMV) and how providers of varying levels of experience use visual feedback (e.g., electronic vital signs) to guide their performance. Background: BVMV is a common and critical procedure for managing pediatric respiratory emergencies. However, providers do not consistently deliver effective BVMV. Efforts to improve BVMV have ignored the question of how providers effectively use feedback often available during BVMV. Method: Six expert and six novice respiratory therapists completed two simulations of an infant requiring BVMV. In one, the technology failed to display SpO2, an important but somewhat redundant visual cue. Eye movements, verbal reports, and ventilation rate (in breaths per minute) were measured in each simulation. Results: Regardless of SpO2 availability, eye movements and verbal reports suggested that novices depended strongly on electronic vital signs and when SpO2 was absent ventilated at a faster rate (exceeding the recommended range of ventilation rates) than when SpO2 was present. Experts' ventilation rates were comparable and within the recommended range in both conditions. When SpO2 was absent, experts emphasized information from direct observation of the patient that novices neglected. Conclusion: Individual differences in the use of feedback during BVMV contribute to the quality of BVMV. This work bears on the theoretical discussions involving the use of automation and nontechnological cues to guide performance. Application: These results have the potential to expand the current understanding of factors underlying effective BVMV with implications for training novice providers.